SISTEM INFORMASI PEMBAYARAN UANG SEKOLAH PADA YAYASAN MI NURUL HIDAYAH KOTA JAMBI - Asrin, Elzas; Megawaty, Merti; Fitrah, Makrami (JURNAL AKADEMIKA, 2024)
MI Nurul Hidayah Jambi City is one of the educational institutions managed by the Nurul Hidayah Foundation whose school payments include tuition payments, Infaq payments, Book payments, Clothes payments, while the payment system is still carried out manually, namely with payment transactions that still use cards. Then it is recorded in the cash book every time the student makes a payment. The weakness of the system is that it is still done manually, sometimes the card is easily torn, damaged or lost, the payment data recap process is still calculated manually from a list previously recorded in the cash book. Another weakness is when students want to pay, they forget to bring a payment card, they only bring money, so an error occurs because the cash book shows that students have not paid. With this problem analysis, researchers provide solutions related to the problems faced by these agencies by developing a payment information system, where the system can make it easier for employees to access all information data about payments and make it easier to make reports. The data to be inputted are class data, teacher data, administrative data, student data and payment data. With outputs in the form of class reports, teacher reports, administrative reports, student reports, payment reports and payment recap reports. With the creation of this payment information system, it is hoped that it will facilitate the administration section in carrying out its duties.